2009
DOI: 10.1186/1471-2180-9-226
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the bacterial diversity among and within individual venous leg ulcers using bacterial tag-encoded FLX and Titanium amplicon pyrosequencing and metagenomic approaches

Abstract: BackgroundApproximately 1 out of every 100 individuals has some form of venous insufficiency, which can lead to chronic venous disease and Venous Leg Ulcer (VLU). There are known underlying pathologies which contribute to the chronic nature of VLU including biofilm phenotype infections.ResultsUsing pyrosequencing based approaches we evaluated VLU to characterize their microbial ecology. Results show that VLU infections are polymicrobial with no single bacterium colonizing the wounds. The most ubiquitous and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(108 citation statements)
references
References 33 publications
(42 reference statements)
1
105
0
2
Order By: Relevance
“…However, surgical site infections posed a unique problem; frequently, the Bacteroides which dominated those wounds required co-growth in a polymicrobial wound biofilm model [37]. In 99 % of wounds, 1 % of the population is easy to grow and is characterized by routine clinical cultures [38].…”
Section: Traumatic Wound Microbiome Workhop 845mentioning
confidence: 99%
“…However, surgical site infections posed a unique problem; frequently, the Bacteroides which dominated those wounds required co-growth in a polymicrobial wound biofilm model [37]. In 99 % of wounds, 1 % of the population is easy to grow and is characterized by routine clinical cultures [38].…”
Section: Traumatic Wound Microbiome Workhop 845mentioning
confidence: 99%
“…It differs from the classic Sanger sequencing, in that it relies on the detection of pyrophosphate release upon nucleotide incorporation, rather than chain termination with dideoxynucleotides (Ronaghi et al, 1998). This deep sequencing technique has been used to evaluate the diversity of microbial populations where thousands of reads/sequences can be www.intechopen.com Skin Grafts -Indications, Applications and Current Research 280 obtained from each sample (Andersson et al, 2007;Bogaert et al;Dowd et al, 2008;Price et al, 2010;Smith et al, 2010;Stewart et al, 2010;Wolcott et al, 2009). …”
Section: Pyrosequencingmentioning
confidence: 99%
“…This means that different microorganisms have more or less favorable growth conditions at different locations which often results in a heterogeneous microbiological distribution throughout the wound (Price et al, 2010). Wolcott (2009) concluded that individual wounds have distinct ecological footprints, and within the individual wounds there can be both significant site specific differences and relative uniformity in the bacterial ecology.…”
Section: Heterogeneous Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…[41][42][43] In general, S. aureus has been visualized more toward the surface of the ulcers and biofilms, particularly compared with Pseudomonas aeruginosa, potentially explaining why S. aureus is most commonly isolated from swab samples of chronic wounds and P. aeruginosa is likely frequently underestimated. 41,43,44 Studies that have used bacterial 16S rRNA sequencing to investigate intrawound variation in chronic wounds include Price et al, 45 and Wolcott et al 46 In both studies, curette samples were collected from different geographic regions of chronic wounds, including the leading edge, opposing leading edge, and/or center of chronic wounds. Wolcott et al concluded there was substantial variation across the wound surface without further statistical analysis.…”
mentioning
confidence: 99%